Job stressors and employee performance / Aidil Qhawarizmie Mekail - Mekail, Aidil Qhawarizmie (Faculty of Business and Management, 2019)
The purpose of this research was to analyze the impact of job stressors with employee performance at Lembaga Pembiayaan Perumahan Sektor Awam (LPPSA). This research is a quantitative research which had used the self-administered electronic questionnaire as the instrument for the collection of data. The data was collected and achieved a percentage of 100% out of the possible 155 respondents which was derived from the total population of 250 employees who work in LPPSA. The data collected was then evaluated by using Statistical Package for the Social Science (SPSS) Version 25 Software. Data was being analyzed to see the frequency of distribution, reliability, descriptive of analysis, correlation between variables and the multiple regression. Finally, the results of this research indicate that all variables (workload, role conflict and work environment) have positive and significant relationship with employee job satisfaction.